2020
DOI: 10.1128/aem.01569-20
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Serovar Typhimurium Temporally Modulates the Enteric Microbiota and Host Responses To Overcome Colonization Resistance in Swine

Abstract: Salmonella enterica serovar Typhimurium is a prevalent incitant of enteritis in human beings and animals. It has been proposed that host defense responses incited by Salmonella allow the bacterium to overcome colonization resistance. Piglets (n=24) were orally inoculated with S. enterica Typhimurium DT104 or buffer alone, and the host and microbial responses were temporally examined at acute (2 days post-inoculation [dpi]), subacute (6 dpi), and recovery (10 dpi) stages of salmonellosis. At the acute stage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 94 publications
(108 reference statements)
2
23
0
Order By: Relevance
“…5 It has also been suggested that specific intestinal segment lesion distribution may be attributed to the lower concentration of bile salts and beta-defensins in the cecum and colon. 2,4,5 The distribution of lesions in different parts of the intestine was similar in cases of P. sordellii and C. perfringens type C infection, which is also consistent with previous descriptions of these diseases. 8,20,27,28 Not surprisingly, the right dorsal colon was the intestinal segment most frequently affected in cases of NSAID intoxication, a disease that is also known as right dorsal colitis.…”
Section: Discussionsupporting
confidence: 90%
“…5 It has also been suggested that specific intestinal segment lesion distribution may be attributed to the lower concentration of bile salts and beta-defensins in the cecum and colon. 2,4,5 The distribution of lesions in different parts of the intestine was similar in cases of P. sordellii and C. perfringens type C infection, which is also consistent with previous descriptions of these diseases. 8,20,27,28 Not surprisingly, the right dorsal colon was the intestinal segment most frequently affected in cases of NSAID intoxication, a disease that is also known as right dorsal colitis.…”
Section: Discussionsupporting
confidence: 90%
“…As one of the most prevalent foodborne pathogens, Salmonella typhimurium infection is associated with impairment of the intestinal barrier and development of the gastrointestinal disease, in which intestinal microbiota is involved [ 5 , 41 , 42 , 43 ]. Several bacteria, such as Akkermansia [ 44 , 45 ], Bacteroides [ 46 ], Alistipes [ 47 ], Prevotellaceae UCG-001 [ 48 ], have been reported to be associated with intestinal barrier dysfunction and intestinal inflammation. In contrast, probiotics, such as Lactobacillus , with the ability to regulate intestinal bacteria of the host has shown improved intestinal barrier and reduced tissue injury [ 5 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“… Salmonella is an opportunistic pathogen that can cause, and then take advantage of, intestinal inflammation to disrupt the commensal microbiota, compromise gut barriers, and colonize host tissues ( 1 3 ). Differences in pre-existing microbial populations may dictate the course and severity of a Salmonella infection ( 4 , 5 ), and successful Salmonella colonization of the host is linked to an inflammation-associated disturbance of the gut microbiota ( 1 3 , 6 , 7 ). Thus, it may be important to support beneficial microbial populations to mitigate Salmonella colonization in pigs.…”
Section: Introductionmentioning
confidence: 99%